The prognostic value of the serum eicosapentaenoic acid to arachidonic acid ratio in relation to clinical outcomes after endovascular therapy in patients with peripheral artery disease caused by femoropopliteal artery lesions. Issue 2 (April 2015) - Hishikari, Keiichi; Kimura, Shigeki; Yamakami, Yosuke; Kojima, Keisuke; Sagawa, Yuichiro; Otani, Hirohumi; Sugiyama, Tomoyo; Kuwahara, Taishi; Hikita, Hiroyuki; Takahashi, Atsushi; Isobe, Mitsuaki
Abstract: Background: The EPA/AA ratio has emerged as a predictor of mortality endpoints in cardiac disease; however, its prognostic value in peripheral artery disease (PAD) patients is unclear. We assessed the serum eicosapentaenoic acid (EPA) to arachidonic acid (AA) ratio in patients with PAD caused by femoropopliteal artery lesions, to determine whether it predicts clinical outcomes after endovascular therapy (EVT). Methods and results: We obtained serum EPA/AA ratios from 132 consecutive patients with PAD caused by femoropopliteal artery lesions before EVT. Patients were divided into two groups using the median value of serum EPA/AA ratios of the entire cohort; LOW group with the levels ≤0.30 (n = 66) and HIGH group >0.30 (n = 66). The incidence of major adverse events (MAE), including major adverse limb events (MALE) and death from any cause, was determined. At a median follow-up interval of 24 months, MALE occurred in 40 patients (30.3%) and 11 patients (8.3%) died. Kaplan–Meier curve analysis demonstrated the survival probability from MAE was significantly worse in patients with EPA/AA ratio under the median (long-rank test χ 2 = 16.4; p < 0.001). Multivariate Cox regression analysis showed critical limb ischemia (hazard ratio [HR]: 3.44; 95% confidence interval [CI]: 1.84 to 6.46; p < 0.001) and the preprocedural serum EPA/AA ratios ≤0.30 (HR: 2.74; 95% CI: 1.33 to 5.65; p = 0.006) independently predicted MAE after EVT. Conclusions: Lower serum EPA/AA ratios appear to be associated with a greater risk of MALE and death from any cause after EVT in patients with PAD caused by femoropopliteal artery lesions. Graphical abstract: Cumulative freedom from risk of major adverse event (MAE) including major adverse limb event and any-cause death after endovascular therapy (EVT) in patients with serum eicosapentaenoic acid to arachidonic acid (EPA/AA) ratio above or below 0.30. Cumulative probability of freedom from MAE were significantly different between the two groups (Mantel-Cox Chi-square = 16.4, P < 0.001). Highlights: The EPA/AA ratio is important for regulating inflammatory mediator production. The EPA/AA ratio is a predictor of mortality endpoints in various vascular diseases. Lower serum EPA/AA ratios associated with a greater risk of MALE and death after EVT. Measuring EPA/AA ratios enables the identification of PAD patients with poor prognosis.